1984
DOI: 10.1289/ehp.8455271
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrinelike (small granule) epithelial cells of the lung.

Abstract: The presence of neuroendocrinelike epithelial cells in the lung of numerous species has been demonstrated by light and electron microscopy. Histochemical methods used to identify these cells have included staining with silver, amine-type fluorescence (APUD cell), periodic acid Schiff (PAS)-lead hematoxylin, and immunohistochemical localization of neuron-specific enolase. Cytoplasmic dense core vesicles (70-200 nm in diameter) have served as the major ultrastructural characteristic. Lung neuroendocrinelike cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 141 publications
1
3
0
Order By: Relevance
“…They had a unique morphology with a central flask-shaped cell body containing the nucleus and single or multiple long, narrow branches that contacted the luminal surface or traveled around and beneath surrounding cells ( Figure 1E ). Consistent with previous studies of PNECs, we found rare cells in SMGs that had dense core vesicles, which are typical neuroendocrine features of PNECs ( Figure 1F ) ( DiAugustine and Sonstegard, 1984 ; Yeger et al, 1996 ). SMG PNECs were also enriched for neurotransmitters and neuropeptides previously reported for PNECs, including calcitonin gene-related peptide (CGRP, the protein of CALCA and CALCB ) and serotonin (5-HT) ( Noguchi et al, 2020 ; Xu et al, 2020 ) ( Figures S1D - S1F ).…”
Section: Resultssupporting
confidence: 92%
“…They had a unique morphology with a central flask-shaped cell body containing the nucleus and single or multiple long, narrow branches that contacted the luminal surface or traveled around and beneath surrounding cells ( Figure 1E ). Consistent with previous studies of PNECs, we found rare cells in SMGs that had dense core vesicles, which are typical neuroendocrine features of PNECs ( Figure 1F ) ( DiAugustine and Sonstegard, 1984 ; Yeger et al, 1996 ). SMG PNECs were also enriched for neurotransmitters and neuropeptides previously reported for PNECs, including calcitonin gene-related peptide (CGRP, the protein of CALCA and CALCB ) and serotonin (5-HT) ( Noguchi et al, 2020 ; Xu et al, 2020 ) ( Figures S1D - S1F ).…”
Section: Resultssupporting
confidence: 92%
“…It has six linked cartilages, a finely controlled array of small muscles and delicate neurovascular supply [ 10 ]. Microscopically, the larynx has ciliated [ 11 ], goblet [ 12 ], brush [ 13 ], small granule [ 14 ] and basal [ 15 ] cells. Damage to any part of this complex structure can affect more than one critical function so its repair is not a simple task, often necessitating choosing one activity to preserve at the expense of the others.…”
Section: Introductionmentioning
confidence: 99%
“…Thin tapering processes extend towards the lumen but do not always reach it within the plane of section [14]. NEC receive vagal innervation; the latter precedes the development of the former by several generations of branching [15,16]. Adult human lung NEC contain gastrin-releasing peptide (the mammalian counterpart of bombesin), calcitonin, leu-enkephalin, and serotonin [17].…”
Section: Introductionmentioning
confidence: 99%
“…Bronchopulmonary NEC are assumed to have paracrine regulatory functions in the fetus [22,23]. Experimental studies have indicated that NEB are indeed intrapulmonary chemoreceptors sensitive to changes in airway gas composition [15], acting via the central nervous system and/or by direct local modulation [24]. With a nerve supply, they could conceivably act as chemoreceptors for respiratory gases, perhaps playing a part in the pulmonary vasoconstrictor [14] and bronchoconstrictor [25] response to hypoxia.…”
Section: Introductionmentioning
confidence: 99%